Current Trends in New Testament Study - Van Voorst, Robert E. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book focuses on seven of the most important formal methods used to interpret the New Testament today. Several of the chapters also touch on Old Testament/Hebrew Bible interpretation. In line with the multiplicity of methods for interpretation of texts in the humanities in general, New Testament study has never before seen so many different methods. This situation poses both opportunities and challenges for scholars and students alike. The articles in this book introduce the latest methods and give examples of these methods at work. The seven methods are as follows: post-colonial, narrative, historical, performance, mathematical analysis of style; womanist; and ecological.